Ivy gourd – Thar Sundari for cultivation in dry-land climate - Samadia, D K; Verma, A K (Indian Horticulture, 2020)
Region-specific vegetable diversity supporting vital nutritious produce to native people. Ivy gourd is most prospective and perennial cucurbit. Its regional variability is not exploited much for developing genotypes suited to high temperature, low moisture stress and resources constraint dry-lands of Rajasthan. With this objectives, targeted germplasm collection was done from 2001–2005 and selected types were studied from 2009 to 2013 at ICAR-CIAH, Bikaner. During spring–summer and rainy–winter season of 2014 to 2016, trait-specific elite-types tested and Thar Sundari exhibited superiority for parthinocarpic fruit yield and marketable quality with 32–45oC day temperature conditions. Tender fruits ready in 6.28–8.42 days from opening of female flowers. Tender fruits are 5.83–6.48 cm length, 1.54–1.89 cm diameter and 11.76–13.54 g weight. Thar Sundari recorded 2.85–3.48 kg/plant/season fruit yield.